"Sometimes I Get So Extremely Tired": Sámi Healthcare Staff Experiences of Cultural Load in Practice - Tove Mentsen Ness; Grete Mehus (SAGE Publishing, 2024)
The study aim was to explore how Sámi healthcare staff experience working as an ethnic minority in the Norwegian healthcare system. This was a qualitative focus group and individual interview study inspired by interpretive description, with 14 participants. The results indicate that Sámi healthcare staff experience various degrees of cultural load in their jobs. This was shown through the two themes: "Feeling responsible for Sámi patients and non-Sámi colleagues" and "Feeling exhausted as a Sámi healthcare worker." To provide culturally safe care for all Sámi patients and their families, it is vital to ensure the well-being of the small number of Sámi healthcare personnel. Therefore, we emphasize the need for training programs for non-Sámi healthcare staff to provide them with the knowledge needed to support their encounters with Sámi patients in culturally safe ways. Sámi healthcare staff cannot take all responsibility for teaching their non-Sámi colleagues and acting as cultural mediators in all situations that non-Sámi staff find challenging. The risk of cultural load and burnout is very present. Nursing departments in universities and leaders in primary and secondary healthcare need to address these issues in order to ensure culturally safe care to all patients and support Sámi healthcare staff.